A rare case of atypical/anaplastic meningioma with MDM2 amplification. (30th May 2018) - Wylleman, Robbert; Debiec-Rychter, Maria; Sciot, Raf
We report the exceptional occurrence of murine double minute clone 2 amplification in an atypical meningioma and its recurrent anaplastic meningioma arising in the right frontal lobe of a 75-year-old man. Murine double minute clone 2 amplification was shown by array comparative genomic hybridization and confirmed by fluorescence in situ hybridization. This is a rare finding with only one similar report in the literature. Awareness of this finding is indicated and should not lead to misdiagnosis of other entities that more commonly show this feature.